Urinary retention after lipoabdominoplasty: case report - Taisa Szolomicki; Caio Engelbrecht de Souza; Semer Ali Mahmoud; Michell Fayad André Haddad; Osvaldo Saldanha Filho; Osvaldo Saldanha (Revista Brasileira de Cirurgia Plástica, 2023)
Introduction: Postoperative urinary retention may predispose to permanent bladder damage. Risk factors include type of anesthesia, type of surgery, and use of anticholinergics, analgesics, and opioids. Once the lesion is established, complementary urodynamic tests are essential for etiological diagnosis and treatment. The objective of this study is to report a case of a patient with urinary retention in the postoperative period of lipoabdominoplasty. Case Report: 27-year-old female patient, without comorbidities or use of continuous medication. She underwent lipoabdominoplasty and evolved postoperatively with urinary retention and bladder distention, diagnosed as detrusor contractility and sensitivity deficit in the urodynamic study. She was maintained in outpatient follow-up with the surgical team and Urology, with a progressive reduction in urinary catheter use and complete removal in eight months of follow-up. Discussion: The objective of aesthetic plastic surgery is to improve the physical appearance of the body. It is subject to complications like other surgical procedures, and pain seems to be the most frequent. Urinary retention may be secondary to the use of opioids, and its diagnosis in the postoperative period of lipoabdominoplasty still has some obstacles. Plication of the rectus muscle diastasis, liposuction, and the use of a compressive abdominal belt make it difficult to identify a possible bladder distention. An episode of bladder overdistention can result in significant morbidity. Conclusion: The present report demonstrated the good evolution of a patient who developed urinary retention in the postoperative period of lipoabdominoplasty. The main diagnostic hypothesis was that it was secondary to the use of opioids.